The Effect Ratio of Pineapple with Melon and Sugar Concentration on The Quality of Ginger Hard Candy - Connie Daniella; Linda Masniary Lubis; Rona J. Nainggolan (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The purpose of this study was to determine the effect of ratio of pineapple and melon and sugar concentration on the quality of hard candy. This study was done by using completely randomized design with two factors, ie : ratio of pineapple and melon (N) (40% : 40%, 45% : 35%, 50% : 30%, 55% : 25%) and sugar concentration (G) (50%, 55%, 60%, 65%). The analyzed parameters were moisture content, vitamin C content, total acid, total soluble solid, ash content, sensory test (color, flavor, taste, and texture). The ratio of pineapple and melon gave significant effect on moisture content, vitamin C content, total acid, total soluble solid, ash content, and sensory test (color, flavor, taste, and texture). The sugar concentration gave significant effect on moisture content, vitamin C content, total acid, total soluble solid, ash content, and sensory test (color, flavor, taste, and texture). The interaction of the ratio of pineapple with melon and sugar concentration had no significant effect on moisture content, ascorbic acid content, total acid, total soluble solid, sensory test (color, taste, and texture), but gave highly  significant effect on ash content, and gave high significant effect on sensory test (flavor). The best composition which gave the best effect on hard candy was 50% : 25% of pineapple ratio with melon and 65%  sugar. Keywords : Ginger, hard candy, ratio of pineapple with melon, sugar concentration